Phallus, performance and power: Crisis of masculinity - Khan, S.; Saggers, Sherry; Hudson-Rodd, N.; Bhuiyan, M.; Bhuiya, A.; Karim, S.; Rauyajin, O. (Carfax Publishing, 2008)
Men’s sexual health concerns (SHCs) receive inadequate attention in research and health interventions. We explored meanings of SHCs, particularly sexual performance, in a qualitative study on male sexuality in Bangladesh. Five focus group discussions with key-informants and 50 urban and rural men were interviewed. Male superiority and power over women were proclaimed as ‘normal’ and ‘natural’. Men’s authoritative relations with women affect sexual acts where ‘real’ men need to be sexually ‘potent’ to demonstrate ‘sexual power’ through sustained penile erections, penetration and prolonged sexual intercourse. Without adequate knowledge of human sexuality, men deem ‘sex’ as another agency of power, dominance and governance. Sexual performance with a large-sized penis symbolizes masculine power to control women. Narrowly focused penetrative male sexuality relies on performance, which destroys the quality of sexual life and equality in relationships. In a patriarchal society, the discrepancy of gender-biased socialization creates an essentialist framework of male sexuality where phallus, performance and power are at the core of men’s SHCs, constructed in the context of market economy and technology. Thus, SHCs, products of men’s threatened masculine power, need to be re-conceptualized before any effective health programs are designed.